2014
DOI: 10.1093/europace/euu325
|View full text |Cite
|
Sign up to set email alerts
|

Patient discomfort following catheter ablation and rhythm device surgery

Abstract: The findings highlight the high prevalence and the poor predictability of moderate-to-severe post-interventional pain within the first 24 h after catheter ablation and cardiac device surgery procedures, despite the use of peri-interventional analgesics. These findings highlight the need for more careful pain assessment and management programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…Although the arterial compression method is generally effective, there are a number of associated difficulties . Bedrest‐associated back pain is a driver of poor patient satisfaction after percutaneous procedures . Further, postoperative bleeding complications of the groin increase with manual compression when patients are on antithrombotic or anticoagulative therapy during cardiac catheterization …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the arterial compression method is generally effective, there are a number of associated difficulties . Bedrest‐associated back pain is a driver of poor patient satisfaction after percutaneous procedures . Further, postoperative bleeding complications of the groin increase with manual compression when patients are on antithrombotic or anticoagulative therapy during cardiac catheterization …”
Section: Introductionmentioning
confidence: 99%
“…2 Bedrest-associated back pain is a driver of poor patient satisfaction after percutaneous procedures. 3 Further, postoperative bleeding complications of the groin increase with manual compression when patients are on antithrombotic or anticoagulative therapy during cardiac catheterization. 1 The introduction of vascular closure devices (VCDs) has improved the speed and efficiency of post-procedure closure.…”
Section: Introductionmentioning
confidence: 99%
“…Device surgeries ( n = 46, 40%) included 19 new implantations of single chamber ( n = 3), dual chamber ( n = 13, in two cases together with explantation of an internal loop recorder) and CRT‐devices ( n = 3), 18 generator replacements due to battery depletion of single chamber ( n = 3), dual chamber ( n = 6) and CRT‐devices ( n = 9), nine revisions of devices with upgrading to dual chamber ( n = 2) and CRT‐devices ( n = 7) together with explantation of two abandoned leads in one case and one device and lead explantation of a CRT‐device due to device infection. The pre‐intervention group is described in detail in (Bode et al., ). The pre‐ and post‐intervention group were comparable in regard to age, gender, the presence of diabetes mellitus and existing chronic pain.…”
Section: Resultsmentioning
confidence: 99%
“…Patients undergoing device surgery also tend to suffer more frequent post‐interventional pain, because they have to cover their wound with a sandbag for several hours to minimize haematoma risk. Bode et al., identified that female gender was associated with early (0–6 h) post‐operative pain. Our analysis was not able to confirm this result.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, the use of pain management guidelines for healthcare workers has been examined (5), as well as communications about pain management with patients following post-operative cardiac surgery (6). Establishing a pain management program (PMP) in a cardiology/electrophysiology (EP) department might seem unnecessary at rst glance because interventions are regarded as minimally invasive (7,8). However, even minor operations/interventions, such as percutaneous cardiac ablative procedures for atrial brillation/ventricular tachycardia followed by bed rest can result in back pain, while implants of pacemakers or cardiac de brillators via incisions can result in unexpectedly high levels of post-operative pain if not adequately treated (7,9).…”
Section: Introductionmentioning
confidence: 99%